Job Stress and Life Satisfaction of College Teachers of Chittagong (Chittagong University Journal of Biological Sciences, 2024)
The purpose of the present study was to investigate the job stress and life satisfaction of college teachers. A total of 100 respondents constituted the sample of the present study. They were elected purposively from different colleges of Chittagong. Bangla version of Life Satisfaction Scale (Ilyas 2001) was used to measure life satisfaction and Bangla version of Job Stress Scale (Rahman and Sorcar 1990) was used to measure job stress. The obtained data were analyzed by using descriptive statistics, t-test and Pearson product moment correlation. Results revealed that the non-government college teachers passes more job stress compared to the government college teachers; the life satisfaction of government college teachers are more compared to the non-government college teachers; teachers whose salary level was tk. 11000 to 20000/- showed more job stress than those whose salary level was more than tk. 20000/-; teachers whose salary level was above tk. 20000/- showed more life satisfaction than those whose salary level ranged from tk.11000 to 20000 /-; Results also showed that job stress was negatively correlated (r = 0.45, p